Emotion regulation mediates the relationship between college students' perceived social support and social anxiety. Issue 4 (4th July 2021) - Yang, Huifang; Li, Junqing; Qiu, Xiaoqing; Zheng, Yuling; Song, Xin
Abstract : We investigated the role of emotional regulation in the relationship between perceived social support and social anxiety. Participants were 547 college students (female = 69%; freshmen = 33%; mean age = 21.13 years, SD = 1.12 years). For the measures, the students completed the Perceived Social Support Scale, the Emotion Regulation Strategies Questionnaire, and the Interaction Anxiousness Scale. Results indicated emotional regulation components of expression suppression to mediate the relationship between perceived social support and social anxiety, lowering levels of social anxiety. People who self-perceived with social support may be less socially anxious believing to be able to express themselves to reduce their social anxiety.